The Potentials of Ergothioneine in the management of diseases in animals - Adah, Adakole (Universitas Airlangga, 2023)
The amino acid histidine is the source of the special nutraceutical ergothioneine (ERG), which is a potent antioxidant. Higher plants and animals, who obtain it from the soil and their food, respectively, do not synthesize it; instead, they obtain it through particular microorganisms, such as actinobacteria and mushrooms. Solute carrier family 22, member 4 (SLC22A4), sometimes referred to as organic cation transporter novel type-1 is an incredibly selective transporter for the substance that is only present in animals (OCTN-1). Depending on how OCTN 1 is expressed in different tissues, particularly in those that are more susceptible to oxidative stress, such as erythrocytes, the buildup of ERG differs. ERG concentration is decreased in a number of chronic inflammatory illnesses, and it appears to have potent cytoprotective actions.It has been certified to be relatively safe by regulatory authorities compared to many other antioxidants.